1982
DOI: 10.1056/nejm198207013070102
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T Cells in Cytomegalovirus Infection

Abstract: We studied 58 recipients of bone-marrow transplants to evaluate immune responses to cytomegalovirus infection. Such infection developed in 43 patients; it was fatal in 12, nonfatal in 23, and present at death from other causes in eight. All patients had low or absent cytomegalovirus-specific cytotoxic lymphocyte activity before the onset of infection. Cytomegalovirus-specific cytotoxic responses developed in all survivors, whereas only two patients with fatal infection had even low-level cytomegalovirus-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 555 publications
(80 citation statements)
references
References 27 publications
1
79
0
Order By: Relevance
“…12,[21][22][23][24] In our study, the use of pre-emptive ganciclovir therapy before day 100 was similar for cases and controls; this factor was thus unlikely to explain the difference in late CMV disease seen in this study. Although continued biweekly surveillance and preemptive therapy was recommended after day 100 for both myeloablative and nonmyeloablative patients, assessing whether surveillance was actually performed was difficult.…”
Section: Discussionmentioning
confidence: 81%
“…12,[21][22][23][24] In our study, the use of pre-emptive ganciclovir therapy before day 100 was similar for cases and controls; this factor was thus unlikely to explain the difference in late CMV disease seen in this study. Although continued biweekly surveillance and preemptive therapy was recommended after day 100 for both myeloablative and nonmyeloablative patients, assessing whether surveillance was actually performed was difficult.…”
Section: Discussionmentioning
confidence: 81%
“…As a positive correlation has been observed between the development of significant levels of nonspecific cytotoxic activity and the recovery of bone marrow and renal transplant patients from HCMV disease, the importance of NK cells in controlling HCMV infection should not be underestimated (Quinnan et al, 1982;Bowden et al, 1987;Venema et al, 1994). If there is heterogeneity in the effectiveness of the NK cell response against HCMV, then it may be possible to control HCMV disease in some instances by the adoptive transfer of NK cell clones, or the use of NK cell stimulatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the cell-mediated immune response to HCMV in host defence has been well documented (Greenberg et al, 1991a, b;Jonjic et al, 1990 He, C. R. Rinaldo Jr and P. A. Morel et al, 1986;Riddell et al, 1992;Quinnan et al, 1984). Several specific targets for T cell recognition during HCMV infection have been recently identified; these include the envelope glycoprotein gB, the matrix protein pp65 and the immediate early IE1 protein (Liu et al, 1988;Alp et al, 1991;Gilbert et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that both humoral and cell-mediated immunity appear to be involved in the host defence against HCMV infection (Quinnan et al, 1984;Rasmussen, 1990). Convalescent human serum contains antibodies that will react with at least 20 different HCMV proteins, which include capsid, tegument, envelope and non-structural viral proteins.…”
Section: Introductionmentioning
confidence: 99%